Effectiveness of an Instructional Program Concerning Healthy Lifestyle on Patients’ Attitudes after Percutaneous Coronary Intervention at Cardiac Centers in Baghdad City - Mousa, Ayad Majid; Mansour, Khalida (Iraqi National Journal of Nursing Specialties, 2020)
Abstract:Objective: The study’s aim to evaluate the effectiveness of instructional program about healthy lifestyle on patients’ attitudes after undergoing percutaneous coronary intervention.Methodology: Quasi-experimental design/ has been utilized for the current study starting from December 2018 to March 2020 to achieve the objectives of the study. Non-probability (purposive) sample of 60 patients was divided into intervention and control groups. Data were analyzed by the application of descriptive and inferential statistical methods.Results: findings reported that before intervention both study and control groups demonstrated low total mean of score related to their attitudes respectively (1.10±0.24 and 1.12±0.25). Significant post-intervention high mean score compared with pre-intervention concerning attitudes of healthy lifestyle for intervention group. Attitudes mean scores for post-intervention was (20.04±3.59 (while pre-intervention was (14.40±2.93). It can be clearly concluded that applied instructional program was effective to improve the level of attitudes significantly for the intervention group participants based on study findings.                               Recommendation: The study recommends specifying a cardiac rehabilitation unit at cardiac centers in Baghdad city to promote healthy lifestyle behaviors for patients after undergoing PCI to improve their quality of life.